Supervising for quality - Lorenzo, Doreen; Goldman, Donna; Kantola, Rick (California : Kantola Productions [publication company] ; Sydney : First Training [distributor])
Teach management skills that will help the managers to fulfill both traditional supervision responsibilities and the manager's responsibilities to encourage employee involvement and continuous quality improvement
Accompanied by 1 instructor's manual and 1 study guide
Presented by Toastmasters International and Kantola Productions
Executive producer, Steve Kantola, Rick Kantola
Keywords: Management -- Quality control